25. STUDY ON THE RELATIONSHIP BETWEEN SARS-COV-2 VARIANTS AND SOME SUBCLINICAL CHARACTERISTICS IN COVID-19 PATIENTS (Vietnam Journal of Community Medicine, 2024)
Objectives: To analyze the realtionship between the SARS-CoV-2 variants and some subclinical characteristics in COVID-19 patients. Subjects: A descriptive, comparative, controlled study analyzing the resutls of SAR-CoV-2 genome sequencing using next generation sequencing technology. Results: We collected 50 samples infected with Alpha, 350 samples infected with Delta and 300 samples infected with Omicron. Among the three variant groups: Ground glass and opacities were highest in the Alpha group, consolidation in the Delta group, and Opacity in the Omicron group (p < 0.05). White blood cells in the Alpha group were lower than others (p < 0.05). The ratio of neutrophils to lymphocytes (NLR) in the Alpha group was lowest (p < 0.05). AST in the Alpha group and ALT in the Delta group was higher than others (p < 0.05). Ferritin was highest in the Alpha group (p < 0.05). Meanwhile, CRP and PCT in the Delta group were highest (p < 0.05). Conclusion: There were differences in lung lesssion between the three SARS-CoV-2 variants. The Delta group had high risk severe laboratories than the others (specially, white blood cell and inflammatory markers). The Alpha group had the highest viral load (Ct) of SARS-CoV-2.
Keywords: SARS-CoV-2 variant, COVID-19, subclinical characteristics.